Odpowiedzi

2009-09-23T20:13:54+02:00
A) (2x - 3)(x+7)=2x²+14x-3x-21=2x²+11x-21
b) (4-5y)(1-6y)=4-24y-5y+30y²=30y²-29y+4
c) -(3+2x)(x-2)=-(3x-6+2x²-4x)=-(2x²-x-6)=-2x²+x+6
2009-09-23T20:17:22+02:00
A) (2x-3)(x+7) = 2x do potegi 2 + 14x - 3x -21 = 11x - 21 + 2x do potegi 2
b) (4-5y)(1-6y) = 4 - 24y -5y - 20y do potegi 2 = 4 - 29y - 20y do potegi 2
c) -(3+2x)(x-2) = -3x + 6 + 2x do potegi 2 - 4x = x + 6 + 2x do ptoegi 2
2009-09-23T20:32:17+02:00
A) (2x - 3)(x+7)=2x²+14x-3x-21=2x²+11x-21
b) (4-5y)(1-6y)=4-24y-5y+30y²=30y²-29y+4
c) -(3+2x)(x-2)=-(3x-6+2x²-4x)=-(2x²-x-6)=-2x²+x+6